Supporting Non-Native English Speakers at the University: A Survey of Faculty & Staff - Peters, Bethany; Anderson, Michael E. (Journal of International Students, 2021)
This study reports on a survey designed to understand the experiences of faculty and staff who work with non-native speakers of English (NNESs) at a U.S. public research university. Over 1,500 faculty and staff responded to the survey, and the findings highlight their perspectives on the benefits of having non-native English speakers on campus, as well as the challenges that they experience in teaching and advising this population of students. We conclude with a discussion about possible resources and strategies that may provide enhanced support for NNES and the faculty and staff who work with them.